Traditional Dwellings Architecture Typology: Resettlement of The Malay Villages in Borneo, Malaysia - Yon Syafni, Samat; NurAkmal Goh, Abdullah; Afzan, Ahmad Zaini; Awang Hasim, Awang Sulong; Zayn Al-Abideen, Gregory; Bambang, Karsono; Dona Rose, Amer Koesmeri; Atta Idrawani, Zaini (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
In recent days, demolition of old buildings in expense of new development is nothing new, especially in the city of Kuching as a large number of old buildings with local heritage values have been recklessly torn down. Some of these buildings held high historical significance and contributed to the character of the city, yet they were not being properly researched, recorded and documented before the eradication. Thus, this study intended to investigate the distinctiveness of the traditional Malay dwellings of Sarawak in 12 traditional villages that are on the verge of being demolished and resettled to a new residential development. The initial stage of the research was done by observing and inventory of five traditional houses which possess significant architectural construction methods and ornamentations. Two architecture typologies of these houses which is the fanlight and railing, were selected and analyzed by comparing with that of the Peninsular Malaysia, in order to determine their similarities and differences. From the analysis, it is found that these Malay traditional houses portray relatively similar architectural typologies, but are slightly different in terms of the patterns for the railing and the minimal geometrical ornamentation of the fanlight. These findings will be used as the basis for the future developments on the research of Sarawak traditional Malay dwellings.